Roteamento dinâmico de veículos: análise do impacto em atividades de prestação de serviço - Lazarin, Daniel França (Universidade Federal de São Carlos, 2008)
In recent years, several studies have been revising static distribution models used by companies in order to incorporate intrinsic dynamic features of transport operations. Thanks to new technologies such as global positioning systems and wireless communications, vehicle routes elaborated in the beginning of the planning horizon can be altered in real time in order to serve new requests, avoid traffic jams, or find alternatives when some of the fleet vehicles are late or broke. In this way, realistic solutions of better quality are expected to be obtained from the company´s point of view (smaller costs) as well as from the customers´ (better service level). The main objective of this work is to analyze the impacts resulting from the incorporation of dynamic vehicle routing and scheduling in service production systems where the due dates for service is a prioritary issue. Specifically, we tackled the Dynamic Vehicle Routing Problem, where route plans are elaborated in a planning horizon. Initially, the definition and characteristics of dynamic problems are presented along with a review of some of the main contributions in the literature. We propose a heuristic based on Pureza and Laporte´s algorithm (2008) in order to obtain routes in real time. The relative impact of the heuristic application to other methods is analyzed by means of a set of generated instances from the data supplied by a drink company in São Paulo State.
Keywords: Problema de roteirização de veículos; Otimização combinatória; Heurística; Logística; Métodos heurísticos; Dynamic vehicle routing; Combinatorial optimization; Heuristics; ENGENHARIAS::ENGENHARIA DE PRODUCAO